2023
DOI: 10.1021/acs.analchem.2c04874
|View full text |Cite
|
Sign up to set email alerts
|

Real-Time Monitoring of Miniaturized Thermal Food Processing by Advanced Mass Spectrometric Techniques

Abstract: Mass spectrometry is a popular and powerful analytical tool to study the effects of food processing. Industrial sampling, real-life sampling, or challenging academic research on process-related volatile and aerosol research often demand flexible, time-sensitive data acquisition by state-of-the-art mass analyzers. Here, we show a laboratory-scaled, miniaturized, and highly controllable setup for the online monitoring of aerosols and volatiles from thermal food processing based on dielectric barrier discharge io… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 29 publications
0
1
0
Order By: Relevance
“…To showcase the utility of DBDIpy, we performed a demonstrational data analysis. The demo data are from a foodomics study where wheat bread was roasted and thermal reaction products were monitored by DBDI-MS ( Weidner et al , 2023 ). It consists of 4196 features.…”
Section: Methodsmentioning
confidence: 99%
“…To showcase the utility of DBDIpy, we performed a demonstrational data analysis. The demo data are from a foodomics study where wheat bread was roasted and thermal reaction products were monitored by DBDI-MS ( Weidner et al , 2023 ). It consists of 4196 features.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, SICRIT has been used to characterize compounds in real-time breath samples, murine brain tissue, yak milk, and car exhaust, to name a few. [7][8][9][10] The results of these studies show that the SICRIT source has the ability to ionize volatile compounds and favors smaller, less polar metabolites, slightly overlapping with electron ionization (EI) (Figure S2). Overall, these studies have demonstrated SICRIT's ability to differentially ionize volatile and nonpolar compounds, and we sought to test whether this source could ionize differential microbial metabolites compared to ESI based ionization of the same extracts.…”
Section: Introductionmentioning
confidence: 99%